(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The article discusses the formation of an assortment of perennials intended for creating gardens in the “Naturgarden” style. The criteria for selecting plants for gardens in a natural style are given. A list of perennials (46 species from the collection of plants of Central Asia of the Main Botanical Garden of the Russian Academy of Sciences (MGB RAS)) that meet these criteria is proposed. For each species, information is provided on the timing of vegetation, flowering and fruiting, methods of reproduction, geographical distribution, life expectancy in the collection, and other characteristics.